Process of Deindustrialization in Montenegro - Marko Tomljanović; Zoran Grubišić; Ivona Huek (Journal of Central Banking Theory and Practice, 2018)
Deindustrialization is a dynamic process that began to attract the attention of economic theorists in the 60s of the 20th century, which is characterized by a reduction in the share of the industrial sector in GDP and employment. A descriptive analysis of the deindustrialization process in Montenegro was carried out. It was established that throughout the observed period, the process of deindustrialization in Montenegro has characteristics present in developed countries. However, a deeper analysis and taking into account the key indicators showed that deindustrialization in Montenegro did not just arise as a sole consequence of positive economic trends. In addition, the entire process took place under the influence of various non-economic indicators. Moreover, the global economic crisis had a significant economic impact on Montenegro's industrial sector. In the process of accession to the EU and in addressing global challenges, the country's industrial sector, in line with key development strategies, is heading towards reindustrialization, i.e. development and progress under changing conditions.
Keywords: F6; L6; 330; deindustrialization; EU; Montenegro; reindustrialization